Letting Go Preparing Yourself to Relinquish Control of the Family Business - Aronoff, C.; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2011)
Letting Go helps family business owners and CEOs make the decision to begin succession planning. It provides new ways of thinking about giving up control of the family business and explores practical strategies for preparing, managing, and carrying out the decision to do so.
Keywords: Management; Organization; Planning; Small business; Leadership; Entrepreneurship; Family-owned business enterprises; Management; Organization; Small Business; Business Strategy/Leadership.; Entrepreneurship; Family Business